The Utility of Neuroimaging Studies for Informing Educational Practice and Policy in Reading Disorders. Issue 147 (March 2015) - Black, Jessica M.; Myers, Chelsea A.; Hoeft, Fumiko
Abstract : Educational neuroscience is an emerging scientific field that brings together researchers from neuroscience, psychology, and education to explore the neurocognitive processes underlying educational practice and theory. In this brief article, we take reading disorder (RD, also known as developmental dyslexia) as an example, and explore trends in neuroimaging research, which may have future implications for educational practice and policy. Specifically, we present two examples that have been central to research efforts in our laboratory: (a) utilizing multimodal neuroimaging to optimize criteria to diagnose RD, and (b) identifying neuroimaging markers that predict future academic outcomes. Such research is faced with important challenges, and rigorous validation is necessary before any claims of the widespread practical utility of neuroimaging can be made. Nevertheless, we contend that neuroimaging studies offer opportunities for providing critical information that could lead to advancing theory of reading and RD. This could in turn lead to better diagnostic criteria and more accurate and earlier identification of RD. © 2015 Wiley Periodicals, Inc.